Tensions on the Nile - Rashid, Wahel (CNRS Éditions, 2023)
19591999201123 March 2015Nile Waters Agreement between Egypt and SudanNile Basin InitiativeConstruction of the Grand Ethiopian Renaissance DamDeclaration of Principles between Ethiopia, Sudan and EgyptThe Nile drainage basin, at 3 million km2, covers 12 countries and is the fourth largest in the world. Over a century, Egypt, the furthest downstream country, exercised a hydro-hegemony, imposing a water management programme on the other countries that was favourable to itself. At the beginning of...